Association of the volume, duration, and intensity of physical activity with incident dementia: A COSMIC collaborative cohort study. (31st December 2021) - Wu, Wanqing; Ding, Ding; Zhao, Qianhua; Xiao, Zhenxu; Ganguli, Mary; Haan, Mary; Lima‐Costa, Maria Fernanda; Costa, Erico; Ng, Tze Pin; Gureje, Oye; Scarmeas, Nikolaos; Brodaty, Henry; et al.
Abstract: Background: Consistent evidence suggested that physical activity (PA) may delay dementia onset. However, the dose‐response association between PA and dementia remains unclear. This study aimed to examine the association between the volume, duration, and intensity of PA and incident dementia among older adults across diverse geographic regions. Method: We harmonized longitudinal data from nine community‐based cohorts in seven countries covering five continents in the Cohort Studies of Memory in an International Consortium (COSMIC). The frequency and duration of performing various PAs per week were collected through questionnaires. Each activity was assigned a metabolic equivalent value (MET). The volume of each PA (MET‐hours) was calculated as the MET multiplied by the hours spent performing the activity. The average PA intensity was calculated as the total volume divided by the total duration hours of PA. Incident dementia was diagnosed after a median of 5.4 years of follow‐up. To explore the dose‐response associations, participants who reported doing regular PA were categorized into subgroups with stratified levels of the volume, duration, or intensity of PA. Multivariate Cox regression models were used to estimate the hazard ratios (HRs) of incident dementia in each group with the lowest volume, duration, or intensity as the reference group. Age, sex, educational year, cohort, APOE, body mass index, smoking, hypertension, diabetes, stroke, and depression were adjusted as the confounders. Result: A total of 8849 participants (51921 person‐years of follow‐up) were included in our analysis. Compared to engaging in low‐intensity activities (2.3≤MET≤3), engaging in moderate to high‐intensity activities was associated with a lower risk of incident dementia (3.00<MET≤4.00, adjusted HR=0.80, 95% CI=0.59‐1.08; MET>4, adjusted HR=0.58, 95% CI=0.40‐0.84; p for trend=0.004) . There was no significant dose‐response relationship between the volume or duration of PA and the risk of incident dementia. Conclusion: Our analysis demonstrated a dose‐response association between PA intensity (but not volume or duration) and dementia risk. This evidence could potentially enrich the current recommendations for the protective effect of PA on dementia onset. While waiting for additional evidence from randomized interventions, older adults may be encouraged to perform a higher intensity of PA to preserve cognition.